REED OSCILLATIONS UNDER THE ACTION OF INERTIAL FORCES - Dremova Nadezhda Vasilievna; Akhmedbekova Alevtina Viktorovna (Journal Park Publishing, 2022)
The article deals with oscillations of natural frequency, while forced oscillations were studied directly by solving a system of differential equations under initial conditions. The method of separation of variables is used to determine the general solution of a homogeneous and a particular solution of a differential equation in partial derivatives of the oscillation of the system "reed - warp threads". The results of a qualitative and quantitative assessment of the oscillation parameters of the system under consideration are given.
Keywords: reed; warp thread; differential equations